SELOC Suzuki outboards 1988-03 repair manual, 2-225 horsepower, 1-6 cylinder - Maher, Kevin M. G. (Seloc Publications, 2005)
SELOC Marine tune-up and repair manuals provide the most comprehensive, authoritative information available for outboard, inboard and stern-drive engines, as well as personal watercraft. SELOC has been the leading source of how-to information for the marine industry since 1974. Designed and written to serve the needs of the professional mechanic, do-it-yourself boat enthusiast, instructor and student, these manuals are based on actual teardowns done by Selocs editors/authors in our on-site facility. Every manual features: -Easy-to-follow, step-by-step, illustrated procedures -Hundreds of exploded drawings, photographs and tables -Troubleshooting sections -Accurate specifications and wiring diagrams Covers all 2-225 Hp, 1 to 4-cylinder, in-line 4, V4 and V6 2-stroke models, including fuel injected units and Jet Drives